The Implementation of Fiqh Principles in the Development of Contemporary Islamic Law - Erna Dewi; Munawarsyah Munawarsyah; Jannus Tambunan; Muhammad Ichsan (Program Pascasarjana IAIN Langsa, 2026)
Fiqh rules, also known as “Qawa’id Fiqhiyyah,” are the result of scholars’ and mujtahids’ efforts, based on the Qur’an and the Prophet’s Hadith, to find solutions to contemporary problems that do not yet have clear rulings. Fiqh principles function as an outline that helps mujtahids and legal experts make decisions on legal matters. Fiqh principles are a tool for ijtihad on problems that have no explicit text in the Qur’an or Hadith. Fiqh principles are very important in applying modern Islamic law because they are used as a benchmark to determine whether a legal ruling is appropriate or not. Islamic legal outcomes pay much attention to aspects of welfare and the avoidance of harm. Ijtihad based on fiqh principles also considers universal interests, so the law is formulated according to time, place, and situation. The statement above strongly supports the idea that qawa’id fiqhiyyah functions as an analytical tool in legal ijtihad. In writing this article, the method used is a literature review, by studying and directly referring to primary and secondary sources on qawa’id fiqhiyyah. This research shows that fiqh principles help integrate textual sources, the objectives of Sharia, and reality, and they play a strategic role in the methodology of ijtihad and the reconstruction of Islamic law. Fiqh principles such as maslahah (public interest), darurah (necessity/emergency situations), istihsan (juristic preference), and maqasid al-shariah (objectives of Islamic law) are highly relevant in finding solutions to contemporary challenges. Improving understanding of fiqh principles is very important for building an Islamic legal system that is flexible, logical, and just, so that Islamic law remains relevant without compromising its core principles, and so that people can apply the law ethically and practically in everyday life.